Beyond lipid-lowering: pleiotropic effects of statins in inflammation, coagulation, and cell proliferation – mechanisms and clinical implications - Kasidid Lawongsa; Yutthana Pansuwan; Supanut Kumjan (Chulalongkorn Medical Journal, 2026)
Statins are widely used lipid-lowering agents that significantly reduce cardiovascular morbidity and mortality through inhibition of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase. Beyond their cholesterol-lowering properties, increasing evidence demonstrates that statins exert several pleiotropic effects independent of lipid reduction. These effects include anti-inflammatory, anti-thrombotic, and anti-proliferative actions mediated primarily through inhibition of the mevalonate pathway and downstream signaling molecules such as Rho, Rac, and Ras. Experimental and clinical studies have suggested potential benefits of statins in various non-cardiovascular conditions, including autoimmune diseases, venous thromboembolism, sepsis-associated coagulopathy, and certain malignancies. In addition, pharmacoepidemiologic studies have provided insights into the real-world effects and safety of statins, including the risk of new-onset diabetes mellitus. This review summarizes the current evidence on the molecular mechanisms and clinical implications of statin pleiotropic effects beyond lipid lowering. However, much of the evidence supporting non-cardiovascular benefits is derived from observational studies, and further randomized controlled trials are required to clarify causality, optimal patient selection, and therapeutic strategies for statin repurposing.